2021
DOI: 10.32607/actanaturae.11063
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Promoters for Gene Therapy

Abstract: Many genetic diseases that are responsible for muscular disorders have been described to date. Gene replacement therapy is a state-of-the-art strategy used to treat such diseases. In this approach, the functional copy of a gene is delivered to the affected tissues using viral vectors. There is an urgent need for the design of short, regulatory sequences that would drive a high and robust expression of a therapeutic transgene in skeletal muscles, the diaphragm, and the heart, while exhibiting limited activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 94 publications
(202 reference statements)
0
23
0
1
Order By: Relevance
“…Due to diffuse cardiac conduction system lesions, guidelines recommend implanting a permanent pacemaker if the patient develops severe bradyarrhythmias ( 15 ). As a result of gaining experience in developing muscle-specific synthetic promoters, scientists can develop constructs that mimic the distinctive expression profile of muscles-specific proteins and fully recover their lost functions ( 16 ). For those with inherited muscle metabolic diseases, this treatment may be particularly useful.…”
Section: Discussionmentioning
confidence: 99%
“…Due to diffuse cardiac conduction system lesions, guidelines recommend implanting a permanent pacemaker if the patient develops severe bradyarrhythmias ( 15 ). As a result of gaining experience in developing muscle-specific synthetic promoters, scientists can develop constructs that mimic the distinctive expression profile of muscles-specific proteins and fully recover their lost functions ( 16 ). For those with inherited muscle metabolic diseases, this treatment may be particularly useful.…”
Section: Discussionmentioning
confidence: 99%
“…121 Likewise, the search for AAV-based treatment of muscular dystrophies motivated development of muscle-specific AAV vectors. 122 Myofiber-specific promoters derived from muscle creatine kinase, α-actin, and desmin genes have shown some specificity and efficacy (reviewed elsewhere 123 ). An additional advantage of using cell type-specific promoters is the propensity for low expression in the liver.…”
Section: Cell-type Promoters and Regulatory Elements To Restrict Tran...mentioning
confidence: 99%
“…An additional advantage of using cell type-specific promoters is the propensity for low expression in the liver. 121,123 Another way of controlling gene expression from viral vectors is by inserting transcriptional regulatory elements or miRNA sequences into the vector. Using repeats of cis-regulatory modules in an AAV vector, Sarcar et al 124 demonstrated robust transgene transcription in muscle.…”
Section: Cell-type Promoters and Regulatory Elements To Restrict Tran...mentioning
confidence: 99%
“…Musclespecific activation of cytokine gene expression would also be informative and potentially applicable in therapeutics, and the CRISPR activation technology (CRISPRa) provides a powerful tool [179]. For instance, the dCas9-SunTag system [180,181] can be combined with appropriate promoters [182] to drive Cre in order to achieve muscle-specific gene activation.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%